2018
DOI: 10.1007/s12029-018-0121-4
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma: Review of Targeted and Immune Therapies

Abstract: Despite the toxicity and low response rate, sorafenib had shown a significant survival benefit in phase III clinical trials, thus encouraging clinical research aimed at advancing the field of molecular therapy. Disrupted signaling pathways related to hepatocellular carcinoma (HCC) include the Wnt/β-catenin, Ras/Raf/MAPK, phosphatidyl inositol 3-kinase/Akt/mechanistic target of rapamycin, hepatocyte growth factor/c-mesenchymal-epithelial transition, IGF, vascular endothelial growth factor, and platelet-derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 87 publications
0
22
0
Order By: Relevance
“…Hepatocellular carcinoma (HCC) is one of the most common malignancies with high mortality and occurrence around the world [1][2][3]. Early diagnosis of HCC is particularly difficult due to the lack of efficient biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is one of the most common malignancies with high mortality and occurrence around the world [1][2][3]. Early diagnosis of HCC is particularly difficult due to the lack of efficient biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that no single protein kinase is mutated at a frequency >5% in HCC (28,29). The majority of targeted therapy (tyrosine kinase inhibitors or monoclonal antibodies) for HCC has demonstrated minimal or no clinical efficacy (30). HCC typically manifests in patients with previous liver damage, commonly caused by chronic hepatitis infection (31).…”
Section: Discussionmentioning
confidence: 99%
“…The mice were kept at the Experimental Animal Center of The Fifth Central Hospital of Tianjin that conforms to international certification standards. A total of 50 BALB/c female athymic mice (aged 6 weeks and weighing 14-16 g) were injected subcutaneously with 5x10 6 HSVtk/Hep3B stem cells. When the subcutaneous tumor volume approached 100 mm 3 , the mice were randomly assigned to five experimental groups (n=10) that received vehicle, SUMO1 plasmid (10 mg/kg), Dex (10 mg/kg), or combined SUMOl plasmid and Dex, while GCV (15 mg/kg) was injected intraperitoneally every other day up to 28 days.…”
Section: G E N E T R a N S D U C T I O Nmentioning
confidence: 99%
“…In recent years, there have been several reports on the development of new delivery systems for traditional chemotherapeutic drugs, such as cytotoxic drugs, new drugs for gene and molecular targets, and their various combinations (5,6). However, due to the resistance of a small proportion of HCC stem cells against chemotherapeutic drugs, almost all currently investigated drugs have failed.…”
Section: Introductionmentioning
confidence: 99%